Genome-wide analysis of the Thaumatin-like gene family in Qingke (Hordeum vulgare L. var. nudum) uncovers candidates involved in plant defense against biotic and abiotic stresses - Wang, Le; Xu, Zepeng; Yin, Wei; Xu, Kai; Wang, Shuai; Shang, Qianhan; Sa, Wei; Liang, Jian; Wang, Li (Frontiers in Plant Science, 2022)
Thaumatin-like proteins (TLPs) participate in the defense responses of plants as well as their growth and development processes, including seed germination. Yet the functioning of TLP family genes, in addition to key details of their encoded protein products, has not been thoroughly investigated for Qingke (Hordeum vulgare L. var. nudum). Here, a total of 36 TLP genes were identified in the genome of Qingke via HMM profiling. Of them, 25 TLPs contained a signal peptide at the N-terminus, with most proteins predicted to localize in the cytoplasm or outer membrane. Sequence alignment and motif analysis revealed that the five REDDD residues required for β-1,3-glucanase activity were conserved in 21 of the 36 Qingke TLPs. Phylogenetically, the TLPs in plants are clustered in 10 major groups. Our analysis of gene structure did not detect an intron in 15 Qingke TLPs whereas the other 21 did contain 1–7 introns. A diverse set of cis-acting motifs were found in the promoters of the 36 TLPs, including elements related to light, hormone, and stress responses, growth and development, circadian control, and binding sites of transcription factors, thus suggesting a multifaceted role of TLPs in Qingke. Expression analyses revealed the potential involvement of TLPs in plant defense against biotic and abiotic stresses. Taken together, the findings of this study deepen our understanding of the TLP family genes in Qingke, a staple food item in Tibet, which could strengthen future investigations of protein function in barley and its improved genetic engineering.